The Anarchist and Terrorist in Indonesia: A Theoretical Reflection - Al Chaidar; Teuku Syahrul Ansari; Irfan Iryadi; Dedy Tabrani (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2019)
In the Indonesian context, acts of anarchism and terrorism by the Jamaah Islamiyah group and the Ansarut Daulah Congregation have a common thread with the Darul Islam movement in Indonesia, especially in relation to acts of violence that claimed human lives. In this case, religious ideology, often accompanied by violence and other forms of emotional expression, became ideological opposition is strong enough, even with a relatively small number of supporters. Indonesia's Islamic ideology in this period appeared in its roughest form: terrorism. Recognition of an act of terrorism suspects Bali Bombing October 12, 2002, a clear expression of religious emotion. Even, Ali Gufron, one of the Bali bombing terror perpetrators, a member of Jamaah Islamiyyah, had expressed his attitude to the firm and simple: as a reply to injustice and tyranny US and its allies against Muslims with the intention that they stop their tyranny.